Pengaruh work-life balance, Lingkungan Kerja dan Kompensasi terhadap Kinerja karyawan PT Gunanusa Eramandiri - Inna Nisawati Mardiani; Alfin Widiyanto (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
This study aims to determine the effect of work-life balance, job satisfaction and compensation on employee performance at PT Gunanusa Eramandiri. The population in this study were all employees of the production section, amounting to 57 employees, using saturated sample techniques. By using data collection methods through questionnaires and secondary data, namely data obtained from companies, data obtained from research is analyzed with quantitative analysis methods, namely multiple regression equations. The results showed that work-life balance has an effect on employee performance. Work environment has an effect on employee performance. Compensation affects employee performance. Furthermore, companies need to increase the share of time, improve environmental conditions and increase benefits, all of which are done to improve employee performance.